Performa Koreksi Bias Prakiraan Curah Hujan Model European Centre Medium Weather Forecast (ECMWF) di Sulawesi - Wenas Ganda Kurnia; Robi Muharsyah; Sofian Widiyanto (Stasiun Pemantau Atmosfer Global Lore Lindu Bariri - Palu, 2020)
Sulawesi has a rainfall pattern consisting of monsoonal, equatorial, and local rainfall patterns, thus causing the difficulty level itself to determine rainfall forecasts in the region. Currently, several rainfall forecast products are available based on models, one of which is the forecast output for the ECMWF System 4 (ECS4) model. The purpose of this research study is to determine the bias in the forecast model of the European Center Medium Weather Forecast (ECMWF) system 4 used in Sulawesi. From the results of the analysis, it was found that the ECMWF system 4 model value has a fairly large bias value in Sulawesi, especially areas that have local and equatorial rainfall patterns such as Central Sulawesi, Gorontalo, eastern South Sulawesi, but for regions such as western and western South Sulawesi. South, North Sulawesi, West Sulawesi and Southeast Sulawesi whose areas have the monsoonal rainfall type, this forecast has a relatively small bias. For the prediction results of ECMWF system 4 after bias correction using Linear Scaling (LS) and Quantile Mapping (QM), it turns out that it has a value close to its observation value, but of the two bias methods, the LS method has the best performance.